Life stories of patients with personality disorders before and after treatment: Change and stability in agency and communion - Pol, Silvia M.; Schug, Fabian; Chakhssi, Farid; Westerhof, Gerben J. (Frontiers in Psychiatry, 2023)
Introduction Studying written life stories of patients with personality disorders (PDs) may enhance knowledge of how they understand themselves, others and the world around them. Comparing the construction of their life stories before psychotherapy to their reconstruction after psychotherapy may provide insight in therapeutic changes in the understandings of their lives. Methods As few studies addressed this topic, the current study explored changes in agency (i.e., perceived ability to affect change in life), and communion (i.e,, perceived connectedness to other persons) in written life stories of 34 patients with various PDs, before and after intensive psychotherapy treatment. Results Life stories showed a positive increase in agency from pre- to posttreatment, in particular regarding internal agency, societal success, and occupational success. No significant changes were observed for communion as a whole. However, the perceived number and quality of close relationships revealed a significant positive increase. Discussion The increased agency in the reconstruction of patients’ life story after psychotherapy suggests that patients improved their perceived ability to affect change in their own lives. This can be seen as an important step in the treatment of PDs towards further recovery.